Improving Knowledge and Awareness of Nonpharmacologic Management of Labor in Medical Students. (October 2015) - Fernandes, Samantha; Vragovic, Olivera; Abbott, Jodi F.
Abstract : STUDY OBJECTIVE: To assess knowledge and awareness of the nonpharmacologic management of labor (NPM) in medical students after participating in an educational module. METHODS: July 2013–May 2014, Boston University School of Medicine students viewed a PowerPoint presentation defining NPM and outlining techniques. Prequestionnaires and postquestionnaires analyzing NPM knowledge and awareness were collected. Four groups of students participated, and data from all four groups were combined; 68 students answered the prequestionnaire and 62 the post. RESULTS: Students were asked to define NPM and provide their responses in multiple-choice format before and after participating in the module. In defining NPM, correct compared with incorrect responses were analyzed using the χ 2 test (SAS 9.4). Correct responses increased from 15% to 79%, P <.001. However, students' stated likelihood to support NPM over epidurals remained unchanged; they preferred offering epidurals considering them a common acceptable practice. CONCLUSION: This educational module effectively defined NPM and outlined techniques but did not change students' self-assessment of their anticipated patient recommendations regarding labor pain management. The lack of traditional evidence-based medicine influenced these responses. Of note, the module did not address students' ability to counsel patients who decline epidurals. A module, which incorporates these elements, could be used to evaluate changes in students' ability to counsel such patients. Our institution, as many do, has the resource of skilled certified nurse midwives incorporated into student experiences and their expertise could be employed to further develop this educational module.